Microbial electrochemical approaches of carbon dioxide utilization for biogas upgrading - Aryal, Nabin; Zhang, Yifeng; Bajracharya, Suman; Pant, Deepak; Chen, Xuyuan (Chemosphere (Oxford), 2022)
Microbial electrochemical approach is an emerging technology for biogas upgrading through carbon dioxide (CO2) reduction and biomethane (or value-added products) production. There is limited literature critically reviewing the latest scientific developments on the bioelectrochemical system (BES) based biogas upgrading technologies, including CO2 reduction efficiency, methane (CH4) yields, reactor operating conditions, and electrode materials tested in the BES reactor. This review analyzes the reported performance and identifies crucial parameters considered for future optimization, which is currently missing. Further, the performances of BES approach of biogas upgrading under various operating settings in particular fed-batch, continuous mode in connection to the microbial dynamics and cathode materials have been thoroughly scrutinized and discussed. Additionally, other versatile application options associated with BES based biogas upgrading, such as resource recovery, are presented. Three-dimensional electrode materials have shown superior performance in supplying the electrons for the reduction of CO2 to CH4. Most of the studies on the biogas upgrading process conclude hydrogen (H2) mediated electron transfer mechanism in BES biogas upgrading. [Display omitted] •Microbial electrochemical approach for biogas upgrading is extensively scrutinized.•Data related to operational parameters for process optimization are discussed.•Applied potential and cathodic catalyst are the keys to reactor performances.•Insight associated with reactor configuration and resource recovery are provided.